Preparation method of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate and its application in sodium ion batteries
By co-doping non-stoichiometric sodium ferric pyrophosphate in the positive electrode material of sodium ion battery and preparing through sol-gel process, the problems of low energy density and unstable structure of the existing positive electrode materials are solved, and high capacity, long cycle life and low cost energy storage effects are achieved.
Patent Information
- Application Number
- CN202310694300.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-06-13
AI Technical Summary
The existing sodium ion battery positive electrode materials have problems such as low energy density, unstable structure, and environmental sensitivity, which are difficult to meet the needs of efficient energy storage.
Mn and Ni co-doped non-stoichiometric sodium ferric pyrophosphate [Na3.12Fe2.44-xMnx/2Nix/2(P2O7)2, X=0.01-1] was used as the positive electrode material, and prepared by a sol-gel process, with surfactant and reverse polar solvent added to improve gel stability and nanoparticle generation.
It significantly improves the theoretical capacity and cyclic stability of the cathode material, enhances the electronic conductivity and reversible discharge capacity, reduces production costs, and is suitable for large-scale production.
Smart Images

Figure CN116621143B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical energy storage, and specifically relates to a preparation method of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate and an application thereof in a sodium ion battery. Background Art
[0002] In recent years, environmental issues have received widespread attention from countries around the world. On the one hand, the use of traditional fossil energy will cause environmental pollution, and on the other hand, it is non-renewable and excessive use will cause energy crisis. Therefore, the development and utilization of new energy has become people's first choice. However, the generation of new energy is easily restricted by climate and environment, and the new energy produced is unstable. Energy storage batteries can store clean energy, and then output and utilize it stably, which solves the problem of unstable clean energy.
[0003] Among various energy storage devices, secondary batteries represented by lithium-ion batteries have been applied to various portable devices in the field of electric vehicles due to their efficient energy conversion and storage equipment, portability, environmental friendliness, high energy density and power density. However, due to the widespread application of lithium-ion batteries, people's demand for lithium mineral resources continues to expand, resulting in an increasingly acute contradiction between the supply and demand of lithium and related lithium salt resources. Therefore, lithium-ion batteries are difficult to become an ideal choice for low-cost energy storage technology. Sodium-ion batteries are considered to be the best choice for large-scale energy storage systems because of their abundant and widely distributed sodium mineral resources and the similar physical and chemical properties of sodium and lithium. Their compounds have great similarities in research methods and applications.
[0004] Like lithium-ion batteries, sodium-ion battery cathode materials have always been a difficult and hot topic in sodium-ion research. In the research of sodium-ion battery cathode materials, people are committed to finding a cathode material with high energy density, good stability, good stability, environmental friendliness and resource conservation. Most polyanion cathode materials have an open three-dimensional skeleton, good rate performance and good cycle performance, but this type of compound has a low theoretical capacity and generally poor conductivity. In order to improve its conductivity and capacity, doping and carbon coating are often used.
[0005] Among sodium-ion cathode materials, layered transition metal oxides, Prussian blue analogs, and transition metal polyanions have received significant attention. Layered metal oxides are sought after due to their high redox potential and energy density. +The insertion / extraction of Prussian blue usually leads to very complex multiphase transitions, resulting in rapid structural degradation of the host material during cycling. In addition, layered metal oxides are very sensitive to the atmosphere and water, making their application a serious problem. Prussian blue analogs, as a metal-organic complex, have a cubic open framework that is conducive to accommodating large-sized Na + , which can reversibly extract two sodiums per structural unit at a high rate. However, these conventionally synthesized compounds always contain a large number of lattice defects and coordinated water, which leads to Na + The huge loss of storage active sites. In addition, the thermally unstable structure also raises concerns about the safety of applied materials. Polyanionic framework compounds based on phosphates, fluorophosphates, sulfates and other new "polyanions" are promising for the development of Na + The new cathode systems provide great opportunities. Different open framework structures, low-energy Na + The presence of migration pathways, the possibility to tune the operating voltage by changing the local environment, and the favorable structural energetics of the voltage response provide some important advantages. In addition, their strong covalent framework makes them thermally stable and ensures impressive oxidative stability at high charging voltages, and among these materials, iron-based pyrophosphates have attracted increasing attention. Their open frameworks and convenient ion transport pathways make them strong candidates for energy storage and conversion. In terms of thermal stability, pyrophosphates may be better than phosphates because the loss of oxygen leads to the condensation of phosphate groups into pyrophosphate groups [P2O7 or (PO 4-x )2]. Therefore, pyrophosphate is considered to be more energetically stable than phosphate at higher temperatures. Triclinic Na2FeP2O7 is used as a cathode material for sodium-ion batteries, which can extract a Na + , the capacity is about 90mAhg -1 Na2FeP2O7 exhibits excellent sodium storage performance, but its low energy density is still the key obstacle to its practical application. Therefore, a series of non-stoichiometric Na2FeP2O7 phases with higher theoretical capacity than the stoichiometric phase Na2FeP2O7 are proposed. 4-a Fe 2+a / 2 (P2O7)2(a=2 / 3-7 / 8) was developed, among which Na 3.12 Fe 2.44 The theoretical capacity of (P2O7)2 can reach 117.6 mAhg -1 Been studied in depth. 3.12 Fe 2.44 The porous coral-like structure of (P2O7)2 not only provides a bicontinuous conductive path for fast electron transport, but the highly porous framework also constructs channels for efficient ion transport. Summary of the invention
[0006] In view of the problems existing in the above-mentioned prior art, the present invention provides a Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate [Na 3.12 Fe 2.44-x Mn x / 2 Ni x / 2 (P2O7)2, X=0.01-1] and its application in sodium ion batteries.
[0007] The preparation method of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate of the present invention comprises the following steps:
[0008] Step 1: Dissolve and stir
[0009] Dissolve metal salt, surfactant, citric acid (the ratio of citric acid to deionized water is 1g:25ml) in deionized water, stir at 40-100°C for 60-600 minutes, then add carbon source and continue stirring for 60-600 minutes, then add sodium phosphate and stir at 40-100°C for 60-600 minutes. The addition of surfactant promotes the dissociation of phosphate to prevent agglomeration and allows various metal salts and sodium phosphate to be fully dissolved in the solvent.
[0010] Step 2: Titration
[0011] Add a reverse polar solvent to the solution obtained in step 1 for titration (add in a ratio of 1:1 with deionized water), and stir until gel is formed after the titration is completed; during the gelation process, the reverse polar solvent is added to replace hydrogen bonds to participate in the reaction between complex molecules, thereby improving the stability of the gel and preventing agglomeration to a certain extent.
[0012] Step 3: Drying
[0013] The gel produced in step 2 is placed in a vacuum drying oven and dried (50-140° C.) to obtain a dry gel.
[0014] Step 4: Pre-sintering
[0015] After grinding the dry gel obtained in step 3, the temperature is raised to 200-400° C. in an inert or reducing atmosphere and kept at this temperature for 60-600 minutes for pre-sintering. Sintering after pre-sintering can make its solid phase reaction more complete.
[0016] Step 5: Sintering
[0017] The pre-sintered product is ground and heated to 400-700° C. in an inert or reducing atmosphere and kept warm for 180-840 minutes to obtain Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate.
[0018] Preferably, in step 1, the metal salt solution is a mixed solution of iron salt, nickel salt and manganese salt, and the addition ratio is mixed according to the ratio of each metal element in the molecular formula. The mass concentration of the metal salt solution is 0.01-20%.
[0019] Preferably, in step 1, the surfactant is one of CTAB, F127, CPC, and BAC.
[0020] Preferably, in step 1, the iron salt and the sodium phosphate salt are mixed in a molar ratio of sodium to iron (2-2.5):3.12.
[0021] Preferably, in step 1, the sodium phosphate salt includes but is not limited to one of sodium dihydrogen phosphate, sodium phosphate and sodium pyrophosphate.
[0022] Preferably, in step 1, the carbon source is one of glucose, sucrose and asphalt, which is added at a mass ratio of 5% to 20% of the product.
[0023] Preferably, in step 2, the reverse polar solvent is one of ethylene glycol and ethanol.
[0024] Preferably, in steps 4 and 5, the inert or reducing atmosphere is one of nitrogen, argon, ammonia, and argon-hydrogen mixed gas.
[0025] Preferably, in step 4, the pre-sintering heating rate is 2-8°C.
[0026] Preferably, in step 5, the sintering heating rate is 5-10°C.
[0027] The method controls the generation of gel and then prepares Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate by step-by-step sintering. The diameter of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate is between 0.01 and 10 μm.
[0028] The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate prepared by the present invention is used as a positive electrode material for a sodium ion battery.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0030] The present invention promotes the dissociation of phosphate radicals by adding a surfactant during the sol-gel process to prevent agglomeration and allow various metal salts and sodium phosphate salts to fully dissolve in the solvent, and adds a reverse polar solvent during the gel process to replace hydrogen bonds to participate in the reaction between complex molecules, thereby improving the gel stability and preventing agglomeration to a certain extent, and promoting the generation of nanoparticles.
[0031] The non-stoichiometric sodium iron pyrophosphate prepared by the present invention has a theoretical capacity (117.6 mAhg -1) is significantly higher than the stoichiometric phase of sodium iron pyrophosphate (97 mAhg -1 ).
[0032] The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate [Na 3.12 Fe 2.44-x Mn x / 2 Ni x / 2 (P2O7)2, X = 0.01-1] material, because Mn ions have higher redox valence and electrochemical activity and partially replace iron ions in the crystal material to increase its capacity, while Ni ions can partially replace iron ions in the crystal material and replace part of the manganese ions in the crystal structure to improve the stability of the structure and keep Mn ions in a higher valence state to inhibit the Jahn-Teller effect brought by it and enhance its cycle life. At the same time, the carbon source added in the sol-gel process is also uniformly coated on the surface of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate. Through the double-doped Na 3.12 Fe 2.44-x Mn x / 2 Ni x / 2 Compared with undoped Na 3.12 Fe 2.44 The capacity and cycle stability of (P2O7)2 have been significantly improved. 3.12 Fe 2.44-x Ni x (P2O7)2(90mAhg -1 )The capacity of dual-doping is still improved.
[0033] The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material involved in the present invention has a simple preparation process, low raw material price, easy operation, and is suitable for large-scale production. The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared by the method has the characteristics of high electronic conductivity, high reversible discharge capacity, high energy density, etc., which lays a good foundation for the further development of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is an X-ray diffraction spectrum comparing the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in Example 1 with the undoped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in the comparative example.
[0035] Figure 2 This is a scanning electron microscope image of the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in Example 1.
[0036] Figure 3This is a cycling performance curve of the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in Example 1 and the undoped non-stoichiometric sodium iron pyrophosphate positive electrode material at a rate of 1 A / g.
[0037] Figure 4 This is a scanning electron microscope image of the undoped non-stoichiometric sodium iron pyrophosphate positive electrode material of the comparative example. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with embodiments and the accompanying drawings. The embodiments are only intended to illustrate the implementation contents of the present invention and are not intended to limit the present invention.
[0039] Embodiment 1:
[0040] This embodiment provides a method for preparing a Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material:
[0041] 1. Weigh 4.04g Fe(NO3)3·9H2O, 0.24g Mn(NO3)2·4H2O, 0.36g Ni(NO3)·6H2O, 0.2g CTAB and 4g anhydrous citric acid and dissolve them in 100ml water. Stir for 8h at 50℃ to obtain a uniform orange-yellow solution. Add 2g glucose and stir for 8h. Then add 4g NaH2PO4·2H2O to the mixture. With the addition of NaH2PO4·2H2O, the solution quickly turns light yellow and continues to stir for 4h. Titrate 40ml ethylene glycol into the mixture. After stirring for 8h, raise the temperature to 100℃ and evaporate the solution to dryness.
[0042] 2. Dry the gel obtained in step 1 at 80° C. in a vacuum drying oven for 24 h, grind the obtained dry gel, heat it to 250° C. in an inert or reducing atmosphere, and keep it warm for 180 minutes for pre-sintering, then grind the pre-sintered product in an inert or reducing atmosphere, heat it to 500° C., and keep it warm for 600 minutes to obtain Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate;
[0043] The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in this embodiment was subjected to an X-ray diffraction (XRD) test, and the test results are as follows: Figure 1 shown.
[0044] The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in this embodiment was tested by scanning electron microscope. The test results are as follows: Figure 2 shown.
[0045] The positive electrode material prepared in this example was mixed with conductive carbon black and PVDF in a ratio of 7:2:1 to form a slurry, coated on a current collector, and cured to obtain a positive electrode for a sodium ion battery. Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material was used as a working electrode, a metal sodium sheet was used as a counter electrode, and a glass fiber was used as a separator. 1 mol L -1 Sodium perchlorate solution (wherein the solvent is a mixture of EC and DEC with a volume ratio of 1:1 and 5% FEC added) was used as the electrolyte, and CR2025 button cells were assembled in an argon-filled glove box for electrochemical performance testing.
[0046] Embodiment 2:
[0047] 1. Weigh 4.04g Fe(NO3)3·9H2O, 0.08g Mn(NO3)2·4H2O, 0.12g Ni(NO3)·6H2O, 0.2g CTAB and 4g anhydrous citric acid and dissolve them in 100ml water. Stir for 8h at 50℃ to obtain a uniform orange-yellow solution. Add 2g glucose and stir for 8h. Then add 4g NaH2PO4·2H2O to the mixture. With the addition of NaH2PO4·2H2O, the solution quickly turns light yellow and continues to stir for 4h. Titrate 40ml ethylene glycol into the mixture. After stirring for 8h, raise the temperature to 100℃ and evaporate the solution to dryness.
[0048] 2. The remaining steps are the same as those in Example 1
[0049] The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate cathode material prepared in this example still has 85 mAh·g at a rate of 1 A / g. -1
[0050] Embodiment 3:
[0051] 1. Weigh 4.04g Fe(NO3)3·9H2O, 0.64g Mn(NO3)2·4H2O, 0.72g Ni(NO3)·6H2O, 0.2g CTAB and 4g anhydrous citric acid and dissolve them in 100ml water. Stir for 8h at 50℃ to obtain a uniform orange-yellow solution. Add 2g glucose and stir for 8h. Then add 4g NaH2PO4·2H2O to the mixture. With the addition of NaH2PO4·2H2O, the solution quickly turns light yellow and continues to stir for 4h. Titrate 40ml ethylene glycol into the mixture. After stirring for 8h, raise the temperature to 100℃ and evaporate the solution to dryness.
[0052] 2. The remaining steps are the same as those in Example 1
[0053] The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate cathode material prepared in this example still has 90 mAh·g at a rate of 1 A / g.-1
[0054] Comparative Example:
[0055] This comparative example provides a non-stoichiometric sodium iron pyrophosphate positive electrode material and a preparation method thereof.
[0056] 1. Weigh 4.04g Fe(NO3)3·9H2O, 0.2g CTAB and 2.88g anhydrous citric acid and dissolve them in 100ml water. Stir continuously at 50℃ for 8h to obtain a uniform orange-yellow solution. Add 2g glucose and stir for 8h. Then add 4g NaH2PO4·2H2O to the mixture. With the addition of NaH2PO4·2H2O, the solution quickly turns light yellow. Continue stirring for 4h. Titrate 50ml ethylene glycol into the mixture. After stirring for 8h, raise the temperature to 100℃ and evaporate the solution to dryness.
[0057] 2. Dry the gel obtained in step 1 at 80° C. in a vacuum drying oven for 24 h, grind the obtained dry gel, heat it to 250° C. in an inert or reducing atmosphere, and keep it warm for 180 minutes for pre-sintering, then grind the pre-sintered product in an inert or reducing atmosphere, heat it to 500° C., and keep it warm for 600 minutes to obtain Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate;
[0058] The non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in this example was subjected to an X-ray diffraction (XRD) test, and the test results are as follows: Figure 1 shown.
[0059] The non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in this example was tested by scanning electron microscope, and the test results are as follows: Figure 4 shown.
[0060] The non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in this example was mixed with conductive carbon black and PVDF in a ratio of 7:2:1 to form a slurry, coated on a current collector, and cured to obtain a sodium ion battery positive electrode. Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material was used as a working electrode, a metal sodium sheet was used as a counter electrode, and a glass fiber was used as a separator. 1 mol L -1 Sodium perchlorate solution (wherein the solvent is a mixture of EC and DEC with a volume ratio of 1:1 and 5% FEC added) was used as the electrolyte, and CR2025 button cells were assembled in an argon-filled glove box for electrochemical performance testing.
[0061] Figure 1 The X-ray diffraction spectrum (XRD diagram) of the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in Example 1 and the undoped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in the comparative example is compared. Figure 1As shown, the diffraction peak position of the XRD image of the material did not change significantly before and after the doping of Mn and Ni ions, and the intensity of its diffraction peak became higher, indicating that the co-doping of Mn and Ni ions made the crystallization of the material more thorough and the degree of crystallization higher.
[0062] Figure 2 This is a scanning electron microscope image of the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in Example 1. Figure 2 As shown, the diameter of the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate particles is about 4.5 um, and they are spherical, and the spherical surface is porous coral-like.
[0063] Figure 3 This is the cycle performance curve of the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared in Example 1 at a rate of 1A / g. Figure 3 As shown in Figure 2, the discharge capacity of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate cathode material is 114 mAh g at 20 mA / g. -1 , close to the theoretical capacity of 117 mAh g -1 , which is better than the undoped non-stoichiometric sodium iron pyrophosphate cathode material in the comparative example, indicating that the doping of manganese ions and nickel ions has played a positive role in improving the material capacity. From the cycle diagram of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate cathode material and undoped non-stoichiometric sodium iron pyrophosphate cathode material at 1A / g rate, it can be seen that the capacity of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate cathode material has not decayed after 300 cycles, and the capacity retention rate is 100%, while the capacity retention rate of undoped non-stoichiometric sodium iron pyrophosphate cathode material after 300 cycles is 94%. At the same time, it can be seen that the material capacity and cycle stability have been improved after Mn and Ni co-doping.
[0064] Figure 4 This is a scanning electron microscope image of the undoped non-stoichiometric sodium iron pyrophosphate positive electrode material of the comparative example. Figure 4 As shown, the undoped non-stoichiometric sodium iron pyrophosphate presents a flaky coral reef structure rather than a spherical porous coral structure after doping.
[0065] According to the sol-gel process involved in this embodiment, a surfactant is added to promote the dissociation of phosphate groups to prevent agglomeration and allow various metal salts and sodium phosphate salts to be fully dissolved in the solvent. In the gel process, a reverse polar solvent is added to replace hydrogen bonds to participate in the reaction between complex molecules, thereby improving the gel stability and preventing agglomeration to a certain extent.
[0066] According to the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material involved in this embodiment, because Mn ions have a higher valence state and electrochemical activity, they partially replace the iron ions in the crystalline material to improve its capacity, and Ni ions can improve the stability of the structure and partially replace the iron ions in the crystalline material and make the Mn ions in a higher valence state to inhibit the Jahn-Teller effect brought by them, thereby enhancing its cycle life. At the same time, the carbon source added in the sol-gel process is also uniformly coated on the surface of the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate, which greatly improves the conductive properties of the material.
[0067] The preparation method of the Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material involved in the above embodiment is simple, has abundant raw materials, and can be mass-produced. The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate positive electrode material prepared by this method has the characteristics of high electronic conductivity, high reversible discharge capacity, good cycle performance, etc., which lays a good foundation for the further development of sodium ion batteries.
[0068] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate, characterized in that The steps include: Step 1: Dissolve and stir Dissolve the metal salt, surfactant and citric acid in deionized water, stir at 40-100°C for 60-600 minutes, then add the carbon source and continue stirring for 60-600 minutes, then add sodium phosphate and stir at 40-100°C for 60-600 minutes; Step 2: Titration Adding a reverse polar solvent to the solution obtained in step 1 for titration, and stirring after the titration until gel is formed; adding a reverse polar solvent during the gelation process to replace hydrogen bonds to participate in the reaction between complex molecules, thereby improving the gel stability and preventing agglomeration to a certain extent; Step 3: Drying The gel produced in step 2 is placed in a vacuum drying oven and dried to obtain a dry gel; Step 4: Pre-sintering After grinding the dry gel obtained in step 3, heating it to 200-400° C. in an inert or reducing atmosphere, and pre-sintering it for 60-600 minutes. Sintering after pre-sintering can make its solid phase reaction more complete. Step 5: Sintering The pre-sintered product is ground and heated to 400-700°C in an inert or reducing atmosphere for 180-840 minutes to obtain Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate Na 3.12 Fe 2.44-x Mn x / 2 Ni x / 2 (P2O7)2, x = 0.01-1; In step 1, the surfactant is one of CTAB, F127, CPC, and BAC; In step 2, the reverse polar solvent is one of ethylene glycol and ethanol.
2. The preparation method according to claim 1, characterized in that: In step 1, the metal salt solution is a mixed solution of iron salt, nickel salt and manganese salt, and the mass concentration of the metal salt solution is 0.01-20%.
3. The preparation method according to claim 1, characterized in that: In step 1, iron salt and sodium phosphate salt are mixed in a molar ratio of sodium to iron (2-2.5):3.
12.
4. The preparation method according to claim 3, characterized in that: The sodium phosphate salt is selected from one of sodium dihydrogen phosphate, sodium phosphate and sodium pyrophosphate.
5. The preparation method according to claim 1, characterized in that: In step 1, the carbon source is one of glucose, sucrose and asphalt.
6. The preparation method according to claim 1, characterized in that: The volume ratio of the reverse polar solvent in step 2 to the deionized water in step 1 is 1:
1.
7. Use of Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate prepared according to any one of the preparation methods of claims 1 to 6, characterized in that: The Mn and Ni co-doped non-stoichiometric sodium iron pyrophosphate is used as a positive electrode material for a sodium ion battery.
Citation Information
Patent Citations
Method for preparing carbon-coated sodium ferric phosphate material
CN105280899A
Positive electrode material for sodium-ion battery and preparation method thereof
CN108046231A